Household Income and Relationships with Different Power Entities as Determinants of Corruption - Asif Reza Anik; Siegfried Bauer (Contemporary Economics, 2014)
This article adds to the corruption literature by identifying factors influencing Bangladeshi farm households' probability of experiencing corruption in different service sectors. The econometric results show that households' probability of being exposed to corruption can largely be explained through their income and their relationship with different power entities. The direction of the relationship between income and corruption vary across services. Relatively rich households have a higher probability of experiencing corruption in sectors such as education, health and electricity. These households are less likely to experience corruption in local government and agricultural extension services. The results here are contrary to the common trend in corruption research that addresses households' aggregate corruption experiences. Households with relationships with different power entities have a lower probability of experiencing corruption than their counterparts without these types of relationships.
Keywords: C3; D1; 330; corruption; income; relationship with power entity; probit model; Bangladeshi farm households